Menukil Bagian Naskah Babad Awak Salira: Nasihat Antarsaudara dan Sistem Konvensi Pupuh Pucung - Arisandi, Isep Bayu; Darsa, Undang Ahmad; Ikhwan (Tambo: Journal of Manuscript and Oral Tradition, 2025)
Manuscript Babad Awak Salira (BAS) is one of the manuscripts in Tatar Sunda that contains ethical values. One of the ethical values is contained in the pucung regarding the recommendation to maintain sibling harmony. Furthermore, the use of pupuh pucung convention in the BAS text shows an intertextual connection with the Javanese pocung form. Therefore, this paper focuses on two main issues: the system of literary conventions and the moral advice concerning sibling relationships. It seeks to answer two key questions: 1) What are the ethical values embedded in the pupuh pucung section of the BAS manuscript? And 2) To what extent does the pupuh pucung convention in BAS intersect with the Javanese pocung tradition? In line with these issues, the aim of this study is to uncover the ethical content of the pupuh pucung section in BAS and to analyze the intersection between the pupuh pucung and pocung literary conventions. This study employs a comparative descriptive-analytical method and incorporates philological approaches for the transliteration and translation of the text. The analysis reveals that the ethical content in the pupuh pucung section emphasizes the role of elder siblings within the family as stand-ins for parental figures. In terms of its literary convention, pupuh pucung in BAS tends to adopt the characteristics of the Javanese pocung form. However, the characters and values expressed remain consistent with Sundanese cultural traits. Moreover, the role of elder siblings is highlighted as one of nurturing and protecting their younger siblings, thereby fostering familial harmony.